A Survey of the health needs and interests of elementary schools pupils in the Division of Cagayan in relation to school health services and their implications to school health instruction - Gunabe, Socorro, (Bacud) 1922- (s.n.], 1967)
The study took the form of a survey of the health needs and interests of elementary school pupils in the Division of Cagayan in relation to the school health service program. It is the purpose of this investigation to determine the educational implications of the findings and to indicate their application on the improvement of the school health service program.